Pengaruh Celebrity Endorser Brand Image dan Kualitas Produk Terhadap Keputusan Pembelian Produk Scarlett Whitening di Kota Batam - Sri Kinanti; Asron Saputra (eCo-Buss, 2023)
This study aims to be able to find out the effect between celebrity endorsers, brand images and product quality on purchasing decisions on Scarlett Whitening products in Batam City. This research uses a quantitative approach with the method. There were 375 respondents taken in this study, with a population of buyers or users who were interested in buying Scarlett Whitening products in Sekupang District, Batam City and aged 15-29 years. Techniques in giving and drawing samples as data researchers utilize purposive sampling. By distributing questionnaires and collecting data, from the distribution the researcher uses a questionnaire on a Likert scale. The data quality test in this study uses the validity and reliability test, the classical assumption test and the influence test in this study uses multiple linear regression analysis and the analysis of the coefficient of determination (R2), while the hypothesis test in this study uses (T test) and (test F ) by using SPSS software program version 25. The results of the coefficient of determination (R2) obtained are the Celebrity Endorser variable, brand image and product quality affect 54.9% on purchasing decisions. From the results of the T test and the F test, it can be concluded that partially the celebrity endorser, brand image and product quality have a significant effect on purchasing decisions, as well as simultaneously celebrity endorser bradn image and product quality has a significant effect on purchasing decisions